Solve the following:
(a) $2\left( 5x-3 \right)-3\left( 2x-1 \right)=9$
(b) $\dfrac{x}{2}=\dfrac{x}{3}+1$
(c) $\dfrac{x}{2}+\dfrac{x}{3}=\dfrac{2x}{5}-1$
Answer
Verified
463.5k+ views
Hint: For answering this question we will use the given expression in each part and arrange all the terms containing $x$ to the left hand side from the right hand side and then simplify it as required per situation and get the value of $x$ .
Complete step by step answer:
Now considering from the question we have the given expression in the first part is $2\left( 5x-3 \right)-3\left( 2x-1 \right)=9$ .
By simplifying the left hand side we will have $10x-6-6x+3=9$ .
By further simplifying we will have $4x-3=9$.
After transferring the like terms aside, that is the non $x$ terms on the right hand side we will have $4x=9+3$ .
So we will have $4x=12$ .
Hence we will have $x=3$ for the first part.
Now considering from the question we have the given expression in the second part is $\dfrac{x}{2}=\dfrac{x}{3}+1$ .
After transferring the like terms aside, that is the $x$ terms on the left hand side we will have $\dfrac{x}{2}-\dfrac{x}{3}=1$ .
By further simplifying the left hand side we will have $\dfrac{3x-2x}{6}=1$ .
By simplifying this we will have $x=6$.
Hence we will have $x=6$ for the second part.
Now considering from the question we have the given expression in the third part is $\dfrac{x}{2}+\dfrac{x}{3}=\dfrac{2x}{5}-1$ .
After transferring the like terms aside that is the $x$ terms on left hand side we will have $\dfrac{x}{2}+\dfrac{x}{3}-\dfrac{2x}{5}=1$ .
By further simplifying the left hand side we will have $\dfrac{3x+2x}{6}-\dfrac{2x}{5}=1$ .
By simplifying this we will have
$\begin{align}
& \dfrac{5x}{6}-\dfrac{2x}{5}=1 \\
& \Rightarrow \dfrac{25x-12x}{30}=1 \\
\end{align}$ .
So we will have $\dfrac{13x}{30}=1$ .
Hence we will have $x=\dfrac{30}{13}$ for the third part.
Note: While answering questions of this type we should take care while performing the calculations for example in the third part if we had made a mistake and written as $\dfrac{25x-12x}{30}=1\Rightarrow \dfrac{12x}{30}=1\Rightarrow x=\dfrac{5}{2}$ which is clearly wrong. The important point that we use here is that the left hand side and the right hand side of an expression are always equal to each other. We can substitute the value of x and then check if the right hand side and left hand side are the same or not.
Complete step by step answer:
Now considering from the question we have the given expression in the first part is $2\left( 5x-3 \right)-3\left( 2x-1 \right)=9$ .
By simplifying the left hand side we will have $10x-6-6x+3=9$ .
By further simplifying we will have $4x-3=9$.
After transferring the like terms aside, that is the non $x$ terms on the right hand side we will have $4x=9+3$ .
So we will have $4x=12$ .
Hence we will have $x=3$ for the first part.
Now considering from the question we have the given expression in the second part is $\dfrac{x}{2}=\dfrac{x}{3}+1$ .
After transferring the like terms aside, that is the $x$ terms on the left hand side we will have $\dfrac{x}{2}-\dfrac{x}{3}=1$ .
By further simplifying the left hand side we will have $\dfrac{3x-2x}{6}=1$ .
By simplifying this we will have $x=6$.
Hence we will have $x=6$ for the second part.
Now considering from the question we have the given expression in the third part is $\dfrac{x}{2}+\dfrac{x}{3}=\dfrac{2x}{5}-1$ .
After transferring the like terms aside that is the $x$ terms on left hand side we will have $\dfrac{x}{2}+\dfrac{x}{3}-\dfrac{2x}{5}=1$ .
By further simplifying the left hand side we will have $\dfrac{3x+2x}{6}-\dfrac{2x}{5}=1$ .
By simplifying this we will have
$\begin{align}
& \dfrac{5x}{6}-\dfrac{2x}{5}=1 \\
& \Rightarrow \dfrac{25x-12x}{30}=1 \\
\end{align}$ .
So we will have $\dfrac{13x}{30}=1$ .
Hence we will have $x=\dfrac{30}{13}$ for the third part.
Note: While answering questions of this type we should take care while performing the calculations for example in the third part if we had made a mistake and written as $\dfrac{25x-12x}{30}=1\Rightarrow \dfrac{12x}{30}=1\Rightarrow x=\dfrac{5}{2}$ which is clearly wrong. The important point that we use here is that the left hand side and the right hand side of an expression are always equal to each other. We can substitute the value of x and then check if the right hand side and left hand side are the same or not.
Recently Updated Pages
Express the following as a fraction and simplify a class 7 maths CBSE
The length and width of a rectangle are in ratio of class 7 maths CBSE
The ratio of the income to the expenditure of a family class 7 maths CBSE
How do you write 025 million in scientific notatio class 7 maths CBSE
How do you convert 295 meters per second to kilometers class 7 maths CBSE
Write the following in Roman numerals 25819 class 7 maths CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science